2016
DOI: 10.1038/ncomms12426
|View full text |Cite
|
Sign up to set email alerts
|

Cingulin and actin mediate midbody-dependent apical lumen formation during polarization of epithelial cells

Abstract: Coordinated polarization of epithelial cells is a key step during morphogenesis that leads to the formation of an apical lumen. Rab11 and its interacting protein FIP5 are necessary for the targeting of apical endosomes to the midbody and apical membrane initiation site (AMIS) during lumenogenesis. However, the machinery that mediates AMIS establishment and FIP5-endosome targeting remains unknown. Here we identify a FIP5-interacting protein, Cingulin, which localizes to the AMIS and functions as a tether mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(107 citation statements)
references
References 58 publications
4
102
0
1
Order By: Relevance
“…While the Exocyst complex is clearly required for this targeting, cingulin (CGN) also recently emerged as an important regulator of Rab11/FIP5-endosome transport to AMIS. In a recently published study, 43 CGN was shown to bind directly to FIP5, thus functioning as a targeting/tethering factor for Rab11/FIP5-endosomes during the early stages of midbody-dependent lumen formation. Moreover, it was shown that both the branched actin cytoskeleton and midbody microtubules are required for the association of CGN with the AMIS.…”
Section: Rab11 During Cell Division and Amis Formationmentioning
confidence: 97%
See 1 more Smart Citation
“…While the Exocyst complex is clearly required for this targeting, cingulin (CGN) also recently emerged as an important regulator of Rab11/FIP5-endosome transport to AMIS. In a recently published study, 43 CGN was shown to bind directly to FIP5, thus functioning as a targeting/tethering factor for Rab11/FIP5-endosomes during the early stages of midbody-dependent lumen formation. Moreover, it was shown that both the branched actin cytoskeleton and midbody microtubules are required for the association of CGN with the AMIS.…”
Section: Rab11 During Cell Division and Amis Formationmentioning
confidence: 97%
“…Since C-terminal tails of glutamylated microtubules bind directly to the basic patch located in the head region of CGN, it is likely that this binding mediates initial CGN recruitment to the midbody. 43 Another interesting finding was that Rac1 activation at the midbody induces the recruitment of WAVE/Scar complex, which then promotes the polymerization of branched actin filaments through the activation of Arp2/3. The polymerization of these branched actin filaments is also obligatory for the formation of the AMIS at the midbody, as well as for the formation and development of a single apical lumen.…”
Section: Rab11 During Cell Division and Amis Formationmentioning
confidence: 99%
“…With regard to how these apical microtubules associate with the AJCs, in TJ‐enriched fractions, several microtubule‐associated proteins have been identified. One of them is cingulin, a ZO‐1–associated protein, which has been examined in detail with respect to its association with microtubules . These findings have led to the idea that the apical microtubules are at least partly associated with the TJ in a combined system, tentatively termed the TJ–apical complex .…”
Section: Apical Microtubule Networkmentioning
confidence: 99%
“…This suggests that the delivery of sialomucins to the apical interface might require other proteins, such as the tight-junction protein cingulin, which the researchers showed was produced upon LIF removal. Cingulin has been implicated in the tethering of vesicles to the apical membrane, indicating that it might have a role in cavity formation 13 . Future work will be needed to identify the cocktail of proteins that is sufficient to trigger naive cells to form a cavity.…”
Section: Early Embryos Kept In Checkmentioning
confidence: 99%